Human lymphocyte subpopulations. Human thymus-lymphoid tissue (HTL) antigen-positive lymphocytes forming rosettes with sheep erythrocytes and HTL antigen-negative lymphocytes interacting with antigen-antibody-complement complexes - Yata, J. (1973)
Human lymphocytes from various lymphoid tissues were studied for the relationship between the existence of HTL (human thymus-lymphoid tissue) antigen, and binding of sheep erythrocytes (E) or sheep erythrocyte–antibody-complement complexes (EA(IgM)C43). E adhered to the majority of thymus lymphocytes and formed rosettes. These lymphocytes were shown to be HTL antigen positive by immunofluorescence performed simultaneously. In the peripheral lymphoid tissues, 10–30% of lymphocytes formed E rosettes and almost all E rosette-forming lymphocytes were HTL antigen positive. Conversely HTL antigen-negative cells did not form E rosettes. In contrast, the cells binding EA(IgM)C43 were always HTL antigen negative. There were very few HTL antigen-positive or rosette-forming lymphocytes either with E or EA(IgM)C43 in bone marrow. From these data we conclude that E-rosette-forming and HTL antigen-positive lymphocytes are of thymus origin and EA(IgM)C43-rosette-forming cells are not thymus-dependent cells.